Mendekatkan Rumput Laut ke Masyarakat: Program Sosialisasi dan Pendidikan untuk Peningkatan Ekonomi Desa Ulidang, Majene - Indah Sari Arbit; Dian Lestari; Erwin Erwin; Suparjo Razasli Carong; Latif Dollah; Purnama Sari (Institut Pertanian Bogor, 2024)
Ulidang Village, part of the Tameroddo Sub-district, has excellent potential in the fisheries and marine sector, although it still faces significant economic challenges. The potential of seaweed as a marine resource that has yet to be fully utilized is the focus of this activity. The main objective is to provide comprehensive counseling on the potential of seaweed, including cultivation methods, nutritional content, and business management aspects. This activity's implementation stage starts with planning, program implementation, and evaluation. The research results showed that socialization efforts, including explanations of seaweed potential, business management, and farming profit simulations, have provided the community with a deep understanding. The pretest and post-test evaluations illustrated the improvement in participants' understanding after the socialization activities. Thus, the development of seaweed farming in Ulidang Village can be a solution to improve community welfare, create jobs, and care for the marine environment. Strategic steps include strong partnerships, community empowerment, and adoption of innovations to ensure the sustainability of seaweed farming at the local and national levels.